e-Dictionaries in a Network of Information Tools in the e-Environment - Bothma, Theo J.D.; Gouws, Rufus H. (Lexikos, 2020)
Traditional dictionaries offer curated data to users. Users should therefore be able to find the correct data to solve their information need. However, users don’t necessarily know the exact scope of lexicographic information. Dictionary articles can still demand considerable interpretation by the user to select the appropriate meaning or equivalent. In the e-environment, users can easily navigate between different e-sources. This is especially evident on various e-book platforms, where one can link multiple dictionaries and other sources to a text or search of the internet. Internet content is obviously not curated, and providing access to such data is therefore anathema to the traditional lexicographer. A traditional dictionary is the result of an application of data pushing procedures. The online environment enables the use of data pulling procedures that give users access to both curated and non-curated data. These issues are illustrated by means of a number of examples that show that a large number of different and disparate information sources are easily available to the user to satisfy any specific information need, and that the dictionary is one of a plethora of information sources. The information is therefore available on demand, without risking information overload. It is argued that, when optimising a network of information tools that constitutes a comprehensive search universe, the information retrieval structure should preferably have a circular network as application domain, rather than a linear continuum.